LEARNING A WRITING POETRY THROUGH PRAGMATIC ANALYSIS - Prasetyo, Dodi Erwin; Hadi, Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Writing is a language skill that is developed through continuous practice, including in poetry writing. However, in instructional practice, poetry writing activities tend to focus mainly on aesthetic aspects of language and have not widely incorporated more contextual linguistic approaches, particularly pragmatic analysis. In addition, scholarly studies integrating poetry writing with a pragmatic perspective remain relatively limited. Therefore, this study aims to explore poetry writing through a pragmatic analysis approach and to examine its contribution to the development of students’ critical thinking and writing skills. This research employs a qualitative approach using a library research method by systematically reviewing textbooks, journal articles, and previous studies relevant to poetry writing and pragmatics. The research stages include collecting relevant literature, analyzing the concepts of writing and poetry, examining pragmatic contexts, and synthesizing the relationship between pragmatics and the poetry writing process. The findings indicate that integrating pragmatic analysis into poetry writing instruction has the potential to enhance students’ ability to generate and develop ideas, understand contextual meanings, and foster critical language awareness. The main conclusion of this study emphasizes that a pragmatic approach can serve as a strategic alternative in poetry writing instruction, with pedagogical implications highlighting the need for collaboration between educators and curriculum developers, as well as opportunities for further research examining the relationship among pragmatics, poetry, and learners’ levels of language proficiency. ABSTRAK Menulis merupakan keterampilan berbahasa yang bersifat terlatih dan memerlukan proses pembiasaan yang berkelanjutan, termasuk dalam penulisan puisi. Namun, dalam praktik pembelajaran, kegiatan menulis puisi masih cenderung terbatas pada aspek estetika bahasa dan belum banyak memanfaatkan pendekatan linguistik yang lebih kontekstual, khususnya analisis pragmatik. Selain itu, kajian ilmiah yang mengintegrasikan penulisan puisi dengan perspektif pragmatik masih relatif jarang ditemukan. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi penulisan puisi melalui pendekatan analisis pragmatik serta mengkaji kontribusinya terhadap pengembangan kemampuan berpikir kritis dan keterampilan menulis peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan, melalui penelaahan sistematis terhadap buku teks, artikel jurnal, dan hasil penelitian terdahulu yang relevan dengan penulisan puisi dan pragmatik. Tahapan penelitian meliputi pengumpulan sumber pustaka, analisis konsep menulis dan puisi, kajian konteks pragmatik, serta sintesis hubungan antara pragmatik dan proses penulisan puisi. Hasil kajian menunjukkan bahwa integrasi analisis pragmatik dalam pembelajaran menulis puisi berpotensi meningkatkan kemampuan siswa dalam menemukan dan mengembangkan ide, memahami konteks makna, serta menumbuhkan kepekaan berbahasa secara kritis. Simpulan penelitian ini menegaskan bahwa pendekatan pragmatik dapat menjadi alternatif strategis dalam pembelajaran menulis puisi, dengan implikasi pedagogik berupa perlunya kolaborasi antara pendidik dan pengembang kurikulum, serta peluang penelitian lanjutan yang mengkaji hubungan pragmatik, puisi, dan tingkat kebahasaan peserta didik.